Biodiversity and metacommunity structure of animals along altitudinal gradients in tropical montane forests. (9th November 2015) - Willig, Michael R.; Presley, Steven J.
Abstract: The study of altitudinal gradients has made enduring contributions to the theoretical and empirical bases of modern biology. Unfortunately, the persistence of these systems and the species that compose them is threatened by land-use change at lower altitudes and by climate change throughout the gradients, but especially at higher altitudes. In this review, we focus on two broad themes that are inspired by altitudinal variation in tropical montane regions: (1) dimensions of biodiversity and (2) metacommunity structure. Species richness generally decreased with increasing altitude, although not always in a linear fashion. Mid-altitudinal peaks in richness were less common than monotonic declines, and altitudinal increases in richness were restricted to amphibian faunas. Moreover, gradients of biodiversity differed among dimensions (taxonomic, phylogenetic and functional) as well as among faunas (bats, rodents, birds) in the tropical Andes, suggesting that species richness is not a good surrogate for dimensions that reflect differences in the function or evolutionary history of species. Tropical montane metacommunities evinced a variety of structures, including nested (bats), Clementsian (rodents, bats, gastropods), quasi-Clementsian (reptiles, amphibians, passerines) and quasi-Gleasonian (gastropods) patterns. Nonetheless, compositional changes were always associated with the ecotones between rain forest and cloud forest, regardless of fauna.